Inhibition of DRP1 Impedes Zygotic Genome Activation and Preimplantation Development in Mice - Li, Yuanyuan; Mei, Ning-Hua; Cheng, Gui-Ping; Yang, Jing; Zhou, Li-Quan (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrion plays an indispensable role during preimplantation embryo development. Dynamic-related protein 1 (DRP1) is critical for mitochondrial fission and controls oocyte maturation. However, its role in preimplantation embryo development is still lacking. In this study, we demonstrate that inhibition of DRP1 activity by mitochondrial division inhibitor-1, a small molecule reported to specifically inhibit DRP1 activity, can cause severe developmental arrest of preimplantation embryos in a dose-dependent manner in mice. Meanwhile, DRP1 inhibition resulted in mitochondrial dysfunction including decreased mitochondrial activity, loss of mitochondrial membrane potential, reduced mitochondrial copy number and inadequate ATP by disrupting both expression and activity of DRP1 and mitochondrial complex assembly, leading to excessive ROS production, severe DNA damage and cell cycle arrest at 2-cell embryo stage. Furthermore, reduced transcriptional and translational activity and altered histone modifications in DRP1-inhibited embryos contributed to impeded zygotic genome activation, which prevented early embryos from efficient development beyond 2-cell embryo stage. These results show that DRP1 inhibition has potential cytotoxic effects on mammalian reproduction, and DRP1 inhibitor should be used with caution when it is applied to treat diseases. Additionally, this study improves our understanding of the crosstalk between mitochondrial metabolism and zygotic genome activation.